2010
DOI: 10.3168/jds.2010-3388
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Comparison of rectal and vaginal temperatures in lactating dairy cows

Abstract: A method commonly used to identify illness in dairy cows is measuring body temperatures with a rectal thermometer, but vaginal measures are becoming common in research. The primary objective of this study was to validate vaginal measures of body temperature by comparing them with rectal temperatures. Data loggers used to collect vaginal temperatures can be programmed to collect many readings per day, providing an opportunity to interpret effects of health in relation to diurnal differences in temperatures. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
90
8
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 21 publications
19
90
8
12
Order By: Relevance
“…According to this definition, it appears that lactating camels are more thermally labile than dry camels. This finding is consistent with the previous studies on dairy cattle which reported that body temperatures of early and/or late lactating dairy cattle are higher than dry cattle (Araki et al, 1984;El-Nouty et al, 1990;Vickers et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to this definition, it appears that lactating camels are more thermally labile than dry camels. This finding is consistent with the previous studies on dairy cattle which reported that body temperatures of early and/or late lactating dairy cattle are higher than dry cattle (Araki et al, 1984;El-Nouty et al, 1990;Vickers et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…These observation emphasize that milking can alleviate the environmental heat stress in dairy cattle. Numerous studies have monitored the circadian rhythm of body temperature in lactating and dry dairy cattle in their natural habitat (Araki et al, 1984;Al-Haidary, 2000;Vickers et al, 2010). Unfortunately, however, the circadian rhythm of body temperature in dairy camels has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…The difference of TT between the morning vs. afternoon is in agreement with those reported by Vickers et al (2010), who measured vaginal temperatures of dairy cows. But differs from those reported by Aharoni et al (2005) who found no differences for rectal temperatures and RR.…”
Section: Discussionsupporting
confidence: 81%
“…Changes in body temperature have been reported to be valuable measurements of the febrile response to an LPS challenge in cattle, and are indices routinely used to monitor the severity of the inflammatory response (Elsasser et al, 1996;Bieniek et al, 1998;Jacobsen et al, 2005;Borderas et al, 2008;Reuter et al, 2008;Carroll et al, 2009;Waggoner et al, 2009a, b). The correlations achieved between rectal and vaginal temperature in the current study are higher than those previously reported in Holstein cows postpartum (r ¼0.81; P o0.001), in postpartum cows with retained placenta (r ¼0.75; Po0.001), or during peak lactation (r¼ 0.46; Po0.001; Vickers et al, 2010) as well as those reported in pregnant dairy cows (r ¼0.95; Hillman et al, 2009). However, Vickers et al (2010) and Hillman et al (2009) used hand-held thermometers to measure rectal temperature, unlike the current study in which rectal and vaginal temperatures were measured using indwelling temperature measuring devices simultaneously in the same animal.…”
Section: Resultscontrasting
confidence: 76%